INFANTRY WEAPONS IN SOUTH AFRICA, 1652-1881 - Hudson, A.L.S. (Scientia Militaria - South African Journal of Military Studies, 2012)
Lt Genl C. L. Viljoen, present Chief of the South African Army, describes the South African soldier in his forword to the book ’Our South African Army Today’ as follows: ’Throughout history, soldiering has always come naturallY to South Africans. In many wars and battles [he South African soldier has proved himself .to be brave, determined and willing to sacrifice all for the cause.’1 It is a well establ ished fact that the infantry was and still is the nucleus of any army and was aptly described by SirWilliam Napier as the ’Queen of the Battlefield.’